DECONSTRUCTING AND MEDIATING THE EXTENSIONS OF SPACE TOWARDS HYBRID REALITIES - Schulke, Bettina (European Scientific Journal, ESJ, 2015)
Our current concept of space is going through a radical change of perception. While some theories proclaim skepticism about the disappearance of space, other theories talk about the extension of space. For millennia of years our perception of space was dominated by a body-focused spatial experience. Today static definitions of visibility are increasingly replaced through a new flexibility, dynamic and mobility. The physical coexists with the electronic space yet at the same time the sensual feeling of space vanishes in the virtual world. Influenced by telematics media and machines we are blurring the boundaries of our physical space towards the virtual reality (VR). As consequence a new form of hybrid spaces appear. Space is no longer exclusively the housing for context anymore, instead networked contexts generates space and extend it towards another dimension. Characterized by immateriality, nonlocation and the leave of the container space new forms and aesthetics appear. This article explores how processes connected with a spatial-specific focus might drastically change in the near future.